Peranan Dinas Pengendalian Penduduk Keluarga Berencana Pemberdayaan Perempuan dan Perlindungan Anak (Dp2kbp3a) Dalam Memberikan Perlindungan Hukum Terhadap Anak Korban Kekerasan Seksual di Kota Tidore Kepulauan - Hasan, Emi; Lego, Indra Rusdian (Peneliti.net, 2025)
This study aims to determine the role of the Population Control Service, Family Planning, Women's Empowerment and Child Protection (DP2KBP3A) in providing legal protection for child victims of sexual violence in Tidore Islands City and to determine the factors that hinder the Population Control Service, Family Planning, Women's Empowerment and Child Protection in providing legal protection for child victims of sexual violence in Tidore Islands City. The research method used is empirical juridical, namely by conducting post-testing and direct interviews in the field with respondents who are considered to play a very important role in accordance with the problems studied by the author. The results of the study illustrate that the importance of the Population Control Service, Family Planning, Women's Empowerment and Child Protection in providing legal protection for child victims of sexual violence in Tidore Islands City in its implementation is not effective, one of the causes is the lack of public knowledge of Regional Regulation Number 4 of 2020 concerning the Protection of Women and Children Victims of Sexual Violence. Legal Protection, Criminal Acts of Sexual Violence, Children